Exploring the impact of cultural values on project performance: The effects of cultural values, age and gender on the perceived importance of project success/failure factors. Issue 3 (25th February 2014) - Chipulu, Maxwell; Ojiako, Udechukwu; Gardiner, Paul; Williams, Terry; Mota, Caroline; Maguire, Stuart; Shou, Yongyi; Stamati, Teta; Marshall, Alasdair
Abstract : Purpose: – This study aims to explore the impact of cultural values on the importance individuals assign to project success/failure factors (PSFFs). Design/methodology/approach: – Themes emerging from 40 interviews of project practitioners based in Brazil, China, Greece, Nigeria, Thailand, the UAE, the UK and the USA are integrated with literature evidence to design a survey instrument. One thousand three hundred and thirteen practitioner survey responses from the eight countries are analysed using multi-group, structural equation modelling. Findings: – Ten project success/failure indicators (PSFIs) are found to reduce to two main PSFFs: project control and extra-organisational goals and project team management/development and intra-organisational goals. It is found that the levels of importance individuals assign to both factors are dependent, not only on age and gender, but also cultural values measured as constructs based on Hofstede's individualism, masculinity, power distance and uncertainty avoidance dimensions. Research limitations/implications: – The snowballing method used to gather survey data and analysis of relationships at individual level reduces generalisability. Practical implications: – The results reveal insights on how best to match the cultural values of project participants to project characteristics. They also increase knowledge on the likely perceptual differences among culturally diverse individuals within projects. Originality/value: – This research contributes to the literature on culture in project environments by defining a factor structure of multiple-dependent PSFIs and increases insight on how specific cultural values may impact on the perception of the so-defined PSFFs.